O Movimento Nacional dos Catadores de Materiais Recicláveis: um movimento em construção 1999-2009 - Silveira, Maria Aparecida da (2010)
The present mastership degree essay has as a purpose to study the National Movement of Catchers of Recyclable Material (MNCR) A movement in progress 1999/2009. The general purpose was to analyze the MNCR, into this decade of existence and action, addressing to its internal organization, external relationships, struggles, limits, and challenges. The subjects of the research were seven people at the front of both national and state board of MNCR and the associations and cooperatives of recyclable materials. Research was conducted by the following question: What is the importance the National Movement of Catchers of Recyclable Material (MNCR)? Conceptual references of the research were: globalization, in Boaventura Santos and Octavio Ianni, work, in Ricardo Antunes and Márcio Pochmann, social movements, in Maria da Glória Gohn and Evelina Dagnino, social policies, in Evaldo Amaro Vieira, Maria Carmelita Yazbek, Ivanete Boschetti and Elaine Rossetti Behring, democratization, em Francisco .C. Weffort and Maria Victória de Mesquita Benevides, all of them conemporary authors in the areas of Social Sciences and Social Work. Methodology used was qualitative survey, being the data collection as an instrument the semistructured interview, based on a scipt. Bibliographical research, survey based on documents and participating observation of the researcher were made too. To interpret data, it was made the following contents analysis. Results of the survey have specially revealed, that what MNCR, after these ten years of existence, was configured as a collective and politic subject, increasingly making, with advancements and challnges, the social inclusion of catchers into social policies, into the productive chain and into international relationships with other organization of catchers